Improving Students’ Technical English Vocabulary Using Readlang Platform at State Polytechnic of Fakfak - Titing Magfirah; Andi Roy; Riyadh Arridha (IHSA Institute, 2022)
Vocabulary is an essential element in learning English which can help students to express their ideas both orally and in writing. However, students at Fakfak State Polytechnic still have limited vocabulary, especially technical English vocabulary. They are difficult to understand the operational terms in English. This study aims to determine whether the use of Readlang platform can improve technical English vocabulary mastery at Informatics Management students in Fakfak State Polytechnic. This research was conducted in one class and applied an experimental research using pretest and posttest group design. The results showed that the students’ mean score increased from 40.28 to 55.78. The hypothesis has been analyzed at a significant level of 0.05, and the results show that the t-value is 8.829 and the sig.2-tailed is 0.000. This means that the alternative hypothesis (Ha) is accepted and the null hypothesis (H0) is rejected, which means that Readlang platform can improve the students' technical English vocabulary. In addition, the questionnare results about students’ perception after using Readlang shows that the majority of students agreed that Readlang platform can increase the students’ enthusiasm in learning vocabulary (92%) and is also effective in helping to remember vocabulary (89.2%), and more importantly is easy to use (96 %).